The therapeutic features of acute kidney injury in the elderly - Blebea, Nicoleta Mirela; Stăniguț, Alina; Mitea, Gabriela (Technium BioChemMed, 2021)
The incidence of acute kidney injury (AKI) is increasing in people of all ages, but patients over the age of 65 are more likely to develop AKI due to structural and functional renal failure associated with aging, comorbidities, and reduced ability to recover. For this reason, the functionality of many organs tends to decrease. Older patients with AKI have an increased risk of mortality in both the short and long term, and survivors are patients with chronic kidney disease (CKD) who eventually progress to end-stage renal disease (ESRD). This paper aims at the therapeutic management of the elderly suffering from AKI. Maintaining adequate hydration and avoiding nephrotoxic agents are helpful in preventing AKI in the elderly. There are no proven treatment measures for AKI in the elderly, except for supportive therapy.